Beginning of the new fishing season - Mumbai Archive Project Team (Jio Institute, 2024)
During the monsoon season, a government-imposed fishing ban lasts for two months. Fishing restarts on Narali Purnima, with the offering of coconuts to mark the auspicious beginning of the new fishing season.